Mini-channel cold plate with nano phase change material emulsion for Li-ion battery under high-rate discharge. (1st December 2020) - Cao, Jiahao; He, Yangjing; Feng, Jinxin; Lin, Shao; Ling, Ziye; Zhang, Zhengguo; Fang, Xiaoming
Graphical abstract: Highlights: A novel cooling scheme by nano emulsion and ultrathin cold plate was presented. Nano emulsion with no subcooling and particle size of 335–360 nm was prepared. Lower Tmax and ΔT were obtained cooled by nano emulsion than cooled by water. Lower Pumping power than water of nano emulsion was obtained. The Tmax and ΔT were below 50 °C and 4 °C in discharge of 9C. Abstract: This paper presents a 4 mm ultrathin mini-channel cooling system based on a nano phase change material emulsion (NPCME) for prismatic Li-ion batteries under high-rate discharge. The NPCME has a larger specific heat capacity than water and no subcooling. Experiments were conducted to compare the cooling performance of water versus NPCME. The results indicate that NPCME can obtain a better cooling effect than water if the inlet temperature is below and near the melting point. At the discharge of 9C, the temperature and temperature difference of the battery pack cooled by 10 wt% NPCME-OP44E were 46 °C and 3.5 °C, compared with 49.5 °C and 4.8 °C under water cooling. Beyond that, the NPCME was able to reach the same cooling performance as water using lower pumping power. The pumping power of the 10 wt% NPCME-OP44E cooling system was only 18.5% that of the water cooling system when the cooling target for the battery temperature difference was 3.5 °C. With regard to charge-discharge duties, the 10 wt% NPCME-OP44E cooling system could limit Tmax and ΔTmax to 45.5 °C and 4 °C throughout all four cycles.